2006
DOI: 10.1177/154230500606000406
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain, Meaning, and Spirituality: A Qualitative Study of the Healing Process in Relation to the Role of Meaning and Spirituality

Abstract: This qualitative study explores experiences of individuals with chronic pain in their attempt to find meaning in the presence of continual pain. Fifteen participants at Loma Linda University Behavioral Medicine Center were interviewed. Emerging themes from this study show that (1) meaning is initially defined as the ability to engage in productive activities and positive relationships; (2) chronic pain is perceived as the factor that removes meaning from the lives of sufferers; (3) medication is used to cope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
15
0
2
Order By: Relevance
“…Aspectos como perdão, experiências espirituais diárias, suporte religioso e autopercepção de religiosidade predisseram significativamente o estado de saúde mental dos pacientes (Rippentrop et al, 2005). Sundblom et al (1994) estudaram por um período de um ano e meio o efeito da cura espiritual em 24 pacientes com síndromes dolorosas crônicas na Finlândia, encaminhados a tratamento espiritual ou a nenhum tratamento. Observaram que houve discreta redução no consumo de analgésicos, melhora na qualidade do sono e que metade (seis pacientes) sentiu alívio após o tratamento.…”
Section: Espiritualidade E Dorunclassified
See 1 more Smart Citation
“…Aspectos como perdão, experiências espirituais diárias, suporte religioso e autopercepção de religiosidade predisseram significativamente o estado de saúde mental dos pacientes (Rippentrop et al, 2005). Sundblom et al (1994) estudaram por um período de um ano e meio o efeito da cura espiritual em 24 pacientes com síndromes dolorosas crônicas na Finlândia, encaminhados a tratamento espiritual ou a nenhum tratamento. Observaram que houve discreta redução no consumo de analgésicos, melhora na qualidade do sono e que metade (seis pacientes) sentiu alívio após o tratamento.…”
Section: Espiritualidade E Dorunclassified
“…O bem-estar físico e o emocional, assim como as relações sociais, familiares e de trabalho, são extremamente afetados (Sorajjakool et al, 2006;Smith et al, 2001). A experiência da dor é mais bem entendida se uma construção multidimensional, incluindo aspectos físi-cos, biológicos, sociais, psicológicos e espirituais, for considerada (Davis et al, 2003).…”
Section: Introductionunclassified
“…However, the proliferation of studies exploring the experience of chronic non-malignant pain 97,140,206,214,250,261,296,327,342,343,348,363,379,385,427,433,[443][444][445][446][447][448][449][450][451][452][453][454][455][456][457][458][459][460] makes it difficult for clinicians and policy makes to use this knowledge to inform practice and policy, and increases the danger that these findings are 'doomed never to be visited'. 27 Research findings need to be accessible if they are to have an effect on care and policy.…”
mentioning
confidence: 99%
“…When pain became chronic, addictions became worse. This finding also occurred in another study where the study participants found that treating their pain with opioids reactivated their former addiction to alcohol or marijuana and expanded their addiction to prescription opioids (Sorajjakool et al, 2006). This study and the Sorajjakool et al (2006) study support the possibility that some individuals treated for pain with opioids may experience an activation of a previous addiction.…”
Section: Discussionmentioning
confidence: 56%
“…In another qualitative study, some participants had a desire to rid themselves of pain with opioids, created a reactivation of their former addiction to alcohol or marijuana, and expanded their use to include prescription opioids (Sorajjakool, Aveling, Thompson, & Earl, 2006). These qualitative studies illustrate the problem of managing pain for those with a coexisting addiction.…”
Section: The Knowledge Deficit When Addiction and Chronic Pain Coexistmentioning
confidence: 99%